Analisis dan Perancangan Sistem Informasi Rekam Medis Poli Gigi (Studi Kasus : Puskesmas Sumbersari Kecamatan Saradan Kabupaten Madiun) - Dzurriyatul Iflahah; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Community health centers(Puskesmas) is one of the most important health services in Indonesia. Puskesmas is a Regional Technical Implementation Unit District / City that have a responsible for organizing health development in a work area. Puskesmas Sumbersari has 4 poly, from these poly, only dentist which have not yet medical record information system. The recording of the patient's medical records is still using manual system by recording the diagnosis / complaint and treatment on the patient's medical record card. With manual medical records archiving is often occurred of damage or loss of patient medical record card, duration of search time and the manufacture of medical record card, and increase the possibility of repetition of data when moving patient's register data from register book to Microsoft Excel. To resolve these problems, a computerized patient-based medical record information system is required to improve the quality of Puskesmas service to patients and to helping doctors in managing medical records data of dental patient of Puskesmas Sumbersari. The purpose of this research is to modeling the business process, analyze the system requirements and design specifications, designing the system interface, and evaluate the results of the requirements specification and design. In the making of analysis and design of information systems, researchers use the method of Object Oriented Analysis and Design which mean in the process of analysis and design using modeling language in the form of Unified Modeling Language. After doing the analysis and design, researcher has to do the evaluation of consistency design in the form of Requirements Configuration Structure and Decision table.